2011
DOI: 10.5897/ajb10.1947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels and particle sizes of perlite on serum biochemical factors of broiler chicks

Abstract: The objective of this study was to investigate the effects of different levels and particle sizes of perlite in broiler chicks' diets on serum biochemical factors. For the stated purpose, 280 day-old Ross 308 broiler chicks were allocated to seven treatments and four replications in a factorial experiment on the basis of randomized complete block design. One factor consisted of two levels (perlite particle sizes of 1.5 and 3 mm) and the other factor included three levels of perlite (1, 3 and 5% of diet). A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Zeolites may cause changes in element absorption, such as Ca and P, as well as electrolyte balance [65]. According to Azar, Adl [66], zeolite levels and physical sizes had no effect on serum Ca, P, Na, and Cl levels. Thus, these results are consistent with Nazifi and Dadras [67] who showed that supplementing broiler diets with natural zeolites (1.2%) had no effect on serum Mg, K, Na, Cl, and levels, but precise changes.…”
Section: Discussionmentioning
confidence: 99%
“…Zeolites may cause changes in element absorption, such as Ca and P, as well as electrolyte balance [65]. According to Azar, Adl [66], zeolite levels and physical sizes had no effect on serum Ca, P, Na, and Cl levels. Thus, these results are consistent with Nazifi and Dadras [67] who showed that supplementing broiler diets with natural zeolites (1.2%) had no effect on serum Mg, K, Na, Cl, and levels, but precise changes.…”
Section: Discussionmentioning
confidence: 99%